Application of ultrasonic vibrations in welding and metal processing: A status review. (April 2017) - Kumar, S.; Wu, C.S.; Padhy, G.K.; Ding, W.
Graphical abstract: Abstract: This review paper aims to introduce systematic in-depth analysis of diversified aspects of ultrasonic application in metal joining and processing including its limitations, future prospects and assessments. Allied welding and metal processing technologies employing ultrasonic vibrations either as the primary source to accomplish the intended operation or as an assistant source to improve the operation efficiency and product quality are classified and discussed. The detailed state-of the art, experimentation and progresses of the ultrasonic vibrations and its applications in the above areas are comprehensively examined, evaluated and presented for exhaustive understandings of its physical mechanism. The ultrasonic vibrations assisted processes claim several advantages such as improved mechanical properties, enlarged process window, higher heat generation, better material mixing and enhanced turbulence etc. over the conventional processes which lead to the remarkable and globalized applications of ultrasonic vibrations in the welding and its allied areas in the present century.